ANXIETY DISORDER AND PSYCHOLOGICAL FACTORS IN ADOLESCENTS - Kahveci, Müedin; Tüner, Tuna (International Scientific Journal Vision, 2022)
Adolescence is when the individual develops and changes physically and spiritually, which begins after childhood. The individual started forming his ideas and thoughts and tried establishing his independence and identity in this period. In this process, the individual grows physically with her biological development and tries to understand her sexist identity with her sexual story. Because she has passed into the abstract period, she also forms her cognitive development.In adolescence, the period when all these developments are experienced, the individual is to gain and create his own identity. With the psychological effect of changes, adolescents are in stress and anxiety. As the state of anxiety causes positive situations in adolescents, this anxiety in which the physical and mental balance cannot establish causes psychological-based disorders. Anxiety disorder is one of them. Anxiety disorder occurs due to genetics, drugs, stress, and chemical substance use. It is a mental and physical disorder that the individual shapes without any relation to reality, has consequences on the adolescent, and affects the development and life functioning of the adolescent. These are panic attack disorder, generalized anxiety disorder, social anxiety disorder, obsessive-compulsive disorder, and separation anxiety disorder. Conditions such as the adolescent's not continuing his education, his family's attitude, and the adolescent's personality traits affect this situation.